Investigation of the myocardial damage due to acute anemia in a rabbit model of acute normovolemic anemia - Tumer, Kenan Cagri; Ozdemir, Haydar; Eroksuz, Hatice (Tubitak Scientific & Technological Research Council Turkey, 2020)
Myocardial damage and increased circulating cardiac troponin I (cTnI) concentrations have been shown in various diseases that cause anemia in animals. Whether the acute anemia that occurs during these diseases directly contributes to myocardial damage and to the release of cTnI to the circulation still remains unclear. The objective of this study was to investigate the effect of acute anemia on myocardial damage and serum cTnI concentration using experimentally-induced acute normovolemic anemia. New Zealand rabbits were randomly separated into 2 groups: an acute anemia group (AG, n = 8) and a control group (CG, n = 6). To induce acute anemia, repeated jugular phlebotomy was performed. Blood samples were collected before the experiment (0) and at 24, 48, 72, 96, and 120 h. Serum cTnI concentrations were measured using a human specific cTnI assay. After the last blood sample was taken, euthanasia was performed to evaluate the histopathological changes and the cTnI immunolabelling in cardiomyocytes. In the AG, the mean packed cell volume (PCV) was 13.1 +/- 1.4% at 120 h. The median serum cTnI concentrations in the AG and the CG were 0.075 (IQR; 0.017-0.077) and 0.015 ng/mL (IQR; 0.01-0.02) at the 120-h mark, respectively (P < 0.01). There was a negative correlation between PCV and serum cTnI concentrations (r = -0.52, P < 0.001). In addition, serum cTnI concentrations were significantly correlated with both the histopathological score (r = 0.75, P < 0.001) and cTnI immunoreactivity (r = -0.79, P < 0.001). The results of this study showed that acute anemia caused histopathological lesions and loss of cTnI immunolabelling in cardiomyocytes, along with an increase in serum cTnI concentrations.
Keywords: Acute normovolemic anemia; cardiac troponin I; myocardial damage; rabbit